Effects of salicylic acid on growth, biochemical constituents in pepper (Capsicum annuutn L.) seedlings - Canakci, S. (My University, 2011)
In the present study, the effect of different concentrations of salicylic acid which is an endogenous organic acid in plants and which is commonly cited as a hormone, on the growth and some other parameters of pepper (Capsicum annuum L. cv.) seedlings was investigated. The solutions were applied to the roots of seedlings using hydroponic method. In general, 1.5 mM concentration of salicylic acid had a stimulating effect while 5 and 10 mM concentrations had varying degrees of inhibitive effects on the seedlings. Although 0.3 mM SA application produced prominent results in the case of all parameters, the difference was not found statistically significant. The inhibitive effect produced by high SA was found much more dominant than the stimulating effect of low SA concentrations. Thus, it was established that SA had a bidirectional physiological effect on the seedlings in a concentration-dependent manner. © 2011 Asian Network for Scientific Information.
Keywords: Growth; Lipid peroxidation; Pepper; Salicylic acid; Toxic effect